2012
DOI: 10.1016/j.rbp.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Clinical Predictors of Retention in Outpatient Alcoholism Treatment

Abstract: Health services should identify the treatment practices and therapists that improve retention. Information about patients' characteristics linked to dropouts should be studied to render treatment programs more responsive and attractive, combining pharmacological agents with more intensive and diversified psychosocial interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
5
0
6
Order By: Relevance
“…Seventy (58%) of the 120 enrolled subjects completed the entire 24 week study which is within the expected range of retention (30 to 60%) for similar studies examining pharmacotherapy in alcohol dependent populations (Correa Filho et al, 2012; Oncken et al, 2001; Prisciandaro et al, 2011); 37 (53%) of the 70 completers were randomized to the BF arm and 33 (47%) were randomized to the PL arm (Table 2). The completion rate was 55% for the PL group and 63% for the BF group and these rates were not significantly different.…”
Section: Resultsmentioning
confidence: 72%
“…Seventy (58%) of the 120 enrolled subjects completed the entire 24 week study which is within the expected range of retention (30 to 60%) for similar studies examining pharmacotherapy in alcohol dependent populations (Correa Filho et al, 2012; Oncken et al, 2001; Prisciandaro et al, 2011); 37 (53%) of the 70 completers were randomized to the BF arm and 33 (47%) were randomized to the PL arm (Table 2). The completion rate was 55% for the PL group and 63% for the BF group and these rates were not significantly different.…”
Section: Resultsmentioning
confidence: 72%
“…Demographic characteristics have predicted dropout in some studies (e.g., younger age: Vuoristo-Myllys, Lahti, Alho, & Julkunen, 2013; male gender: Schilling and Sachs, 1993), whereas other studies have failed to identify significant demographic predictors (e.g., age: Ray, Hutchison, & Bryan, 2006; gender: Elbreder, de Souza e Silva, Pillon, & Laranjeira, 2011; Vuoristo-Myllys, Lahti, Alho, & Julkunen, 2013). Similarly, comorbid depression has been identified as a predictor of AD treatment dropout in some studies (e.g., Filho & Baltieri, 2012) and found unrelated to dropout in other studies (e.g., Kavanagh et al, 2006). Perhaps most illustrative of all, some studies have found that baseline drinking severity is associated with higher dropout (e.g., Graff et al, 2009), other studies have found it to predict lower dropout (e.g., Ray, Hutchinson, & Bryan, 2006), and still others have found it to be unrelated to dropout from AD treatment (e.g., Filho & Baltieri, 2012).…”
mentioning
confidence: 83%
“…Similarly, comorbid depression has been identified as a predictor of AD treatment dropout in some studies (e.g., Filho & Baltieri, 2012) and found unrelated to dropout in other studies (e.g., Kavanagh et al, 2006). Perhaps most illustrative of all, some studies have found that baseline drinking severity is associated with higher dropout (e.g., Graff et al, 2009), other studies have found it to predict lower dropout (e.g., Ray, Hutchinson, & Bryan, 2006), and still others have found it to be unrelated to dropout from AD treatment (e.g., Filho & Baltieri, 2012). …”
mentioning
confidence: 83%
“…Histórico de tratamentos anteriores (13) 8. Dificuldade de comparecer em decorrência do trabalho (46) TOTAL 32…”
Section: Dimensão Tratamentounclassified